Pengaruh Efektivitas Perputaran Piutang dan Perpustaran Kas terhadap Rentabilitas Ekonomi pada Koperasi Karyawan PT. Djarum Kudus - Ibrahim, Chanafi; Winahyuningsih, Panca; Thoha, Achmad (Jurnal Sosial Budaya, 2011)
The main problem in this study were 1) whether there is influence between the effectiveness of economic turnover to  profitability in PT.Djarum Employees Cooperative Spirit? 2) whether there is influence between cash turnover effectiveness  of economic   Profitability on PT.Djarum Employees Cooperative Spirit?The purpose of this study were: 1) to examine the effect of turnover between the effective-ness of economic profitability at  PT.Djarum Kudus Employees Cooperative, 2) to examine the effect of cash turnover between the effectiveness of economic  profitability at PT.Djarum Kudus Employees Cooperative. Data collection methods used in this study is the documentation. That method of data collection by performing recording  based on data obtained from the documents in PT.Djarum Employees Cooperative. With the results of this study as follows. 1.The effectiveness of accounts receivable turnover (X1) proved to have  a  positive  and   significant   impact  on    economic  profitability (Y) this is indicated from the results of the t test which proved the value of each regression coefficient 7.404 each  variable is greater when compared with the value of t 2.920 t count table located in the area rejected (Ho), meaning that zero  hypothesis (Ho) is rejected and alternative hypothesis (Ha) accepted. So the hypothesis presented in this study proved that the effectiveness of the accounts receivable turnover has a significant effect on economic profitability variables. 2.Effectiveness of cash turnover (X2) proved to have a positive and significant impact on eco-nomic profitability (Y) this is indicated from the results of the t test which proved the value of each regression coefficient 3.459 each variable is greater when compared with the value of t 2.920 t count table located in the area rejected (Ho), meaning that zero hypothesis (Ho) is  rejected and alternative hypothesis (Ha) accepted. So the hypothesis presented in this study proved that the effectiveness of  cash turnover has a significant effect on economic profitability variables.